2016
DOI: 10.1021/acs.nanolett.6b00062
|View full text |Cite
|
Sign up to set email alerts
|

Weakened Flexural Strength of Nanocrystalline Nanoporous Gold by Grain Refinement

Abstract: High density of grain boundaries in solid materials generally leads to high strength because grain boundaries act as strong obstacles to dislocation activity. We find that the flexural strength of nanoporous gold of grain size 206 nm is 33.6% lower than that of grain size 238 μm. We prepared three gold-silver precursor alloys, well-annealed, prestrained, and high-energy ball-milled, from which nanoporous gold samples were obtained by the same free-corrosion dealloying process. Ligaments of the same size are fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 48 publications
0
18
1
Order By: Relevance
“…Various aspects of the mechanical properties of NPG have been experimentally studied in bending [8,9], compression [10,11], tension [12,13], indentation [9,14] and non-contact ultrasonics [15]. Computational studies have used mechanics of materials approaches based on a -unit-cell‖ of the NPG structure [16][17][18], finite element methods (FEM) [16,19] and molecular dynamics (MD) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Various aspects of the mechanical properties of NPG have been experimentally studied in bending [8,9], compression [10,11], tension [12,13], indentation [9,14] and non-contact ultrasonics [15]. Computational studies have used mechanics of materials approaches based on a -unit-cell‖ of the NPG structure [16][17][18], finite element methods (FEM) [16,19] and molecular dynamics (MD) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The hardness and elastic modulus of nanoporous silver with different ligament size are also determined at the same indentation depth of 1000 nm. Relationships of hardness and elastic modulus versus ligament size of nanoporous silver as well as nanoporous gold [10,[21][22][23][24][25] are plotted in Fig. 5 for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Biener's research [9] demonstrates that nanoindentation hardness and compressive strength of nanoporous gold depend strongly on ligament size in a way not described by the conventional Gibson–Ashby scaling model. Gwak [10] investigated the mechanical behaviours of nanoporous gold with different densities of initial dislocations and grain boundaries by nanoindentation and three‐point bending test. The results showed that high density of grain boundaries do not strengthen nanoporous gold.…”
Section: Introductionmentioning
confidence: 99%
“…Machined precursor alloys were annealed at 800 °C for 24 hours to release residual stress introduced during mechanical polishing and machining. Samples were immersed in 35% nitric acid solution at 80 °C for 72 hours with stirring, producing np-Au with ligament size of 130 nm 37, 38 . Ligament sizes were measured by diameter of ligament necks, possibly thinnest part, from at least 100 measurements on SEM images.…”
Section: Methodsmentioning
confidence: 99%